Imperfectly perfect universe? Emerging natural order in Thomas Aquinas - Roszak, Piotr (HTS teologiese studies, 2022)
Scientific data indicate that violence is involved in the emergence of higher forms of life from lower forms. This seems incompatible with the God of Christian revelation, who is the source of love and mercy. Current attempts to explain this tension usually focus on two approaches: the ‘gift of freedom’ (McLeish) or the ‘only way’ theory (Southgate). I will argue that Thomas Aquinas’ understanding of nature is able to provide an interesting framework for the challenges posed by the way of the appearance of life. The article will present Aquinas’ theology of nature, which seems to fit perfectly with the current state of scientific knowledge, especially when considering the relationship between God and creation.Contribution: The article shows that the problem of the interpretation of paradise in the Christian tradition may be related to the influence of the Neoplatonic tradition, which reduces paradise to the idealistic sphere. Attention is drawn to the concept of perfection, which does not mean the absence of any disvalue in the natural world, but is a relational concept. The death of animals and natural evil need not be explained by moral evil, but requires a broader interpretation of the value of the natural order.